Etnisitas, Demokrasi Lokal, dan Komunikasi Politik: Praktik Mobilisasi pada Pilkada Maluku Tengah - Hijrah, Hijrah; Lestaluhu, Said; Jaali, La (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This article explores the intersection of ethnicity, local democracy, and political communication in the context of the 2017 regional election (Pilkada) in Central Maluku Regency, with a specific focus on political mobilization practices in Leihitu District. The study investigates how inter-ethnic relations—particularly between the Leihitu and Seram communities—shaped strategic patterns of political communication in advancing local political interests. Employing a qualitative methodology, data were collected through in-depth interviews with key informants directly involved in the processes of political communication and mobilization. Findings indicate that ethnic sentiment played a pivotal role in forming strategic alliances between the Leihitu and Seram ethnic groups. Political communication unfolded in three key phases: the establishment of ethnic organizations as platforms for regional autonomy aspirations; elite consolidation during the pre-candidacy phase; and the mobilization of support for the “empty box” option during the campaign stage as a form of resistance to entrenched political dynasties. These practices illustrate that political communication functioned not merely as a vehicle for information exchange, but as a mechanism for collective identity-based mobilization and resistance. This study offers a novel contribution by demonstrating how ethnic-based political communication can reconfigure local political power through the articulation of shared agendas, such as demands for regional autonomy and opposition to dynastic politics. The findings underscore the importance of recognizing ethnic dynamics in local democratic processes, highlighting the need for decentralization policies that ensure social justice and effective political representation at the grassroots level.